Real Process Improvement Using the CMMI - West, Michael (CRC Press, 2009)
Real Process Improvement Using the CMMI presents readers with non-academic, real-world approaches to process improvement via CMMI. The author provides concepts and techniques for CMMI-based process improvement which are as effective as they are innovative. Professionals at all levels from system engineers to CEOs will find a wealth of practical guidance and new ways to look at model-based process improvement that have already benefited large and small organizations in a variety of environments. Using plain language and enlightening illustrations, the author identifies the most critical concepts of the CMMI, and explains how to turn those concepts into real process improvement. This book provides you with key information that will significantly benefit all CMMI process improvement efforts. Topics include: · Ways to discover and understand the business goals and drivers for successful process improvement initiatives · How to recognize the structures and practices many organizations already have in place that can accelerate process improvement, even before they begin using the CMMI · Planning and managing the process improvement project · Innovative, untraditional yet highly effective and proven strategies for CMMI-based process improvement · A thorough debunking of many of the costly and wasteful myths surrounding CMMI-based improvement